NATIONAL QUALIFICATIONS FRAMEWORKS: THE CURRENT STATE OF PLAY - Mospan, Nataliia (Continuing Professional Education: Theory and Practice, 2019)
This paper presents the current state of higher education in the European Union, namely the process of development and implementation of European Qualifications Frameworks with the National Qualifications Framework in member countries of the European Union. It introduses the analysis of data in all member states mostly based on the reports of the European organizations. This paper also shows that different countries have different strategies and they are on different stages of this process